2013
DOI: 10.1371/journal.pone.0078687
|View full text |Cite
|
Sign up to set email alerts
|

Low Incidence of Spontaneous Type 1 Diabetes in Non-Obese Diabetic Mice Raised on Gluten-Free Diets Is Associated with Changes in the Intestinal Microbiome

Abstract: Human and animal studies strongly suggest that dietary gluten could play a causal role in the etiopathogenesis of type 1 diabetes (T1D). However, the mechanisms have not been elucidated. Recent reports indicate that the intestinal microbiome has a major influence on the incidence of T1D. Since diet is known to shape the composition of the intestinal microbiome, we investigated using non-obese diabetic (NOD) mice whether changes in the intestinal microbiome could be attributed to the pro- and anti-diabetogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 26 publications
3
94
0
1
Order By: Relevance
“…The mechanisms by which early gluten exposure influences the immune system are not fully understood. Evidence from animal models suggests a complex interplay between dietary factors and gut microbiome being relevant in the disease pathogenesis [7]. Results from the BABYDIET cohort further support these findings by demonstrating that the gut microbiome changes markedly during the first year of life and is strongly affected by breastfeeding and solid food introduction [8].…”
Section: Discussionmentioning
confidence: 69%
“…The mechanisms by which early gluten exposure influences the immune system are not fully understood. Evidence from animal models suggests a complex interplay between dietary factors and gut microbiome being relevant in the disease pathogenesis [7]. Results from the BABYDIET cohort further support these findings by demonstrating that the gut microbiome changes markedly during the first year of life and is strongly affected by breastfeeding and solid food introduction [8].…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, a similar microbial shift was shown in a study of diabetic mice, which found 28% reduction in the Lachnospiraceae family and a 54% reduction in the Oscillibacter genus in diabetic versus nondiabetic mice (McDermid, 2012). At the meantime, previous studies also found increased Barnesiella in dietary gluten induced hyperglycemia and Type 1 diabetes of non-obese diabetic mice (Marietta et al, 2013), and in NASH-prone mice which developed hepatic macrovesicular steatosis (Le Roy et al, 2013). Most notably, it should be mentioned that the mice in the MC-LR-treated group did show signs of NASH (unpublished data).…”
Section: Discussionmentioning
confidence: 90%
“…However, in a recent study, NOD mice were raised on either gluten-containing chows (GCC) or gluten-free chows (GFC). GFC-fed mice had a significantly reduced incidence of hyperglycaemia, which was associated with changes in bacterial genera compared to the GCC-fed mice [51]. While the effects of gluten on disease development in a human trial were different than in the NOD study, these studies show the feasibility of early dietary interventions in T1D and the further need to study whether and if these interventions alter the microbiota and associated effects on immunoregulation and disease development.…”
Section: Therapeutic Targeting Of the Gut Microbiome To Block T1d Promentioning
confidence: 82%